Astronomiya kursın xabar-kommunikaciyalıq texnologiyaları ortalıǵında oqıtıw metodikası (ulıwma astronomiya bólimin oqıtıw mısalında) (SCIENCE and SOCIETY, 2021)
The article discusses the advantages of information and communication technologies in the educational process, pedagogical skills of a teacher in the educational process.